Analysing the capacity to respond to climate change: a framework for community-managed water services. (21st October 2019) - Kohlitz, Jeremy; Chong, Joanne; Willetts, Juliet
ABSTRACT: In this paper, we present a conceptual framework for guiding interdisciplinary research on analysing the capacity of community-managed water services to respond to disturbances from climate change. Climate change poses a serious threat to the sustainable delivery of community-managed water services in developing countries. We synthesized key concepts from the latest research on vulnerability and resilience theories into a shared framework that functions as a heuristic for the analysis of different elements of the capacity to respond to climate disturbances and how they are related to community-managed water services. Primary elements of the framework include conceptualisations of the capacities to respond to specific hazards (e.g. through risk management and knowledge of thresholds) and to disturbances in general (e.g. through agency, social structure, and adaptive management practices), the potential for capacity to be differentiated across scales, and the social and biophysical system characteristics that influence capacity to respond to climate change. We describe how each these elements relate to sustaining community-managed water services against climate change throughout the paper. We also discuss subjective choices (temporal frame, system boundaries, scale of inquiry, and desired forms of capacity) that analysts must make when considering how capacity to respond to climate change is analysed.